2022
DOI: 10.1038/s42003-022-03179-1
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the functional role of membrane confinements in TNF-mediated signaling by multiscale simulations

Abstract: The interaction between TNFα and TNFR1 is essential in maintaining tissue development and immune responses. While TNFR1 is a cell surface receptor, TNFα exists in both soluble and membrane-bound forms. Interestingly, it was found that the activation of TNFR1-mediated signaling pathways is preferentially through the soluble form of TNFα, which can also induce the clustering of TNFR1 on plasma membrane of living cells. We developed a multiscale simulation framework to compare receptor clustering induced by solub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 82 publications
0
6
0
Order By: Relevance
“…It has been posited that the conformational dynamics of membrane-bound TNF are restricted and, therefore, generally less favored to bind to the TNFR1 receptor. 67 The most striking difference seen here is on the release of MIF, where vesicular TWEAK is almost 4-fold more potent than soluble TWEAK. On the other hand, the release of CXCL1 is seen only in the presence of soluble TWEAK.…”
Section: Discussionmentioning
confidence: 74%
“…It has been posited that the conformational dynamics of membrane-bound TNF are restricted and, therefore, generally less favored to bind to the TNFR1 receptor. 67 The most striking difference seen here is on the release of MIF, where vesicular TWEAK is almost 4-fold more potent than soluble TWEAK. On the other hand, the release of CXCL1 is seen only in the presence of soluble TWEAK.…”
Section: Discussionmentioning
confidence: 74%
“…Soluble TNF-α functions are mediated through TNFR1 and TNFR2 and, interestingly, it has been shown that TNFR1-mediated signaling pathways predominantly occur via the soluble form of TNFα. Additionally, this soluble form has the capacity to initiate the clustering of TNFR1 on the plasma membrane of living cells [ 40 ].…”
Section: Molecular Structure Receptors and Metabolismmentioning
confidence: 99%
“…It was found that the structures of dimeric TNFR are steadier than monomeric receptor and are favored under acidic conditions (Roy 2017, 2019). In our former work, we have further shown that the conformational dynamics of mTNFα can be significantly changed by these constraints which further affect the spatial–temporal features in clustering of TNFR1 relative to the sTNFα system (Su et al 2022). Based on these preliminary studies, here we further hypothesize that while TNFR1 system prefers sTNFα‐induced clustering to membrane‐bound ligands, the clustering of mTNFα‐bound TNFR2 at cell interfaces is more favorable due to the changes of conformational dynamics under membrane confined condition.…”
Section: Introductionmentioning
confidence: 95%